Business Model Canvas : AFZ Enterprise / Afiqah Anati Abd Aziz - Abd Aziz, Afiqah Anati (2020)
This report has been dedicated to discuss the business canvas model of Clip Tower Air Cooler, one of air cooler machines. In this regard, the key partners of the business have been discussed and along with a list of supplies as well. The key services provided by such partners include the manufacturing, assembly and distribution of company’s products. The company is creating value through provision of latest technology products and by handling customer’s needs and complains. The company distributes its products with the help of different retail store, retail outlets and online stores. It is operating with many sources amongst them the key sources are the people who are employees of the company, its physical assets and intellectual properties